IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS E-LEARNING DAN PENGARUHNYA TERHADAP PENINGKATAN MOTIVASI BELAJAR DAN HASIL BELAJAR MAHASISWA - Ningrum, Rahma Farah (JURNAL LENTERA ICT, 2014)
Referring to the results of the World Summit on the Information Society council (WSIS), is a forum meeting / summit the leaders of these countries in the world in order to build the information society centered on the human, inclusive and development-oriented. That is said to realize a shared vision of the Information Society for ourselves and for future generations, that young people are the future workforce and the primary creators and early adopters of information and communication technology (ICT). Therefore they must be empowered as learners, developers, contributors, work, employers, and policy makers. This research aims to test whether the implementation of media-based learning e-learning can provide influence on student motivation and learning outcomes. The concept of the method used in this study is descriptive survey method. While the method of determination of respondents using structured random sampling method (stratified random sampling) with the number of respondents is 80 students. The variables used were learning motivation and learning outcomes as the dependent variable, while e-learning as an independent variable. While testing the hypothesis proposed in this paper by using data analysis techniques, namely SEM (Structural Equation Modeling) which is operated by using the AMOS program ver. 16. Keywords : E-learning, Learning Motivation, Learning Outcomes, SEM (Structural Equation Modelling)